Intestinal parasites of the bobcat (Lynx rufus) in areas surrounding Queretaro, Mexico - Camacho-Macías, Brenda; Hernandez-Camacho, Norma; Cantó Alarcón, Germinal Jorge; Muñóz-García, Claudia Irais; Pineda-López, Rubén; Pineda-López, Raúl Francisco; Zamora-Ledesma, Salvador; Moreno-Pérez, Marco Antonio (THERYA, 2018)
The bobcat (Lynx rufus) is one of the carnivores most widely distributed in North America, coexisting with wild and domestic animals. Parasites reported for the bobcat in the United States and Canada are generalists typical of the order Carnivora. In Mexico, studies on parasites of carnivorous mammals are scarce due to their elusive nature, which makes difficult to obtain biological samples. Considering the available information about the bobcat in its northern distribution range, the community of intestinal parasites of this species was expected to comprise generalist parasites. The primary aim of this study was to determine the composition of the community of intestinal parasites in the bobcat (Lynx rufus) inhabiting areas surrounding the city of Queretaro, and investigate whether seasonal differences exist. The study was carried out in four sampling sites where Lynx rufus had been previously reported. Tracks were surveyed for scats in the rainy and dry seasons. Scats were analyzed using the Ritchie method supplemented with coprocultures and larval migrations. Parasites were identified based on specialized literature and prevalence was expressed in percentage. A X2 test and a non-metric multidimensional scaling analysis were conducted to compare parasite species composition between sites and between seasons. A total of 83 scat samples were collected, 53 in the rainy season and 30 in the dry season. A total of seven parasite species were identified: Trichuris vulpis, Physaloptera praeputialis, Toxascaris leonina, Toxocara cati, Strongyloides stercolaris, Ancylostoma sp. and Uncinaria stenocephala. The prevalence of parasitized scats in both seasons was 75.9 %, with 73.6 % and 80 % in the rainy and dry seasons, respectively. The X2 test showed no significant differences between seasons (X2 = 0,553, d. f. = 1, P = 0.457). No differences were found in parasite species composition, either between seasons or between localities, according to the nonmetric multidimensional scaling analysis. The parasitic load of the bobcat in areas surrounding Querétaro is composed of generalist nematodes that are typical of carnivores. T. vulpis is recorded for the first time in L. rufus for Mexico. A high prevalence of S. stercolaris was observed, suggesting an interaction with human populations and domestic and wild animals, as reported in other studies on this same carnivore. This study is one of the first reports published on intestinal parasites of L. rufus in anthropic areas of Mexico, finding that the composition and structure of the parasite communities of this carnivore may indicate tolerance to disturbance derived from human activities.